A Case of Primary Multifocal Cutaneous Mucormycosis in a Pediatric Patient with Newly Diagnosed Acute Lymphoblastic Leukemia - Denis Niyazi; Milena Belcheva; Stoyan Vergiev; Valeria Kaleva; Temenuga Stoeva (Medicina, 2023)
Mucormycosis, caused by the widespread molds of the Mucorales order, is an insidious infection that manifests in different clinical forms. Even the most benign form, the cutaneous mucormycosis, can present with severe complications and a fatal outcome in patients with a suppressed immune system and underlining comorbidities. We present a rare case of a proven primary multifocal cutaneous mucormycosis in a child with newly diagnosed acute leukemia without multiorgan dissemination. Various laboratory techniques (histopathological, cultural and molecular-genetic) were used to detect and confirm the diagnosis. Etiological therapy (liposomal amphotericin B, 5 mg/kg) combined with surgical intervention were used to manage the infection. The case shows that a rapid and complex diagnostic approach is of crucial importance for the timely initiation of adequate therapy, as well as for the successful management of this life-threatening fungal infection.